WATER CHEMISTRY ANALYSIS IN RSG-GAS SECONDARY COOLING SYSTEM - Rahayu Kusumastuti; Diyah Erlina Lestari; Sriyono Sriyono; Geni Rina Sunaryo (SIGMA EPSILON - Buletin Ilmiah Teknologi Keselamatan Reaktor Nuklir, 2016)
The G.A Siwabessy reactor (RSG-GAS) located in the Puspiptek area uses water as a coolant. The water as a coolant will contact directly with the component or structure of the reactor, that a chemical reac- tion between water and those components might cause the possibility of corrosion process. Therefore, cooling water quality will determine the integrity of reactor components or structures. The research described in this paper was conducted in order to monitor the quality of secondary cooling water, so that the water quality specifications is maintained and the reactor can be safely operated. One way to monitor the cooling water quality is by performing analysis into the secondary cooling water and raw water on June 6, 2016. The methodology used was by analysing the pH value using a pH-meter, conductivity value using Conductivity-meter, water hardness analysis, and analysis for some chemical elements such as Cl-, SO42-, Fe, P using calibrated Spectrophotometer DR / 2400. Corrosion rate of the carbon-steel as the piping material of secondary cooling system under environmental corrosion condition was also analyzed using the Potentiostat. From those performed analysis, the overall measured values are still below the standard values as required in the RSG-GAS safety analysis report document, meaning that the water quality management of the secondary coo- ling system has been well performed so far.